Respiratory failure: technical means for diagnosis and respiratory support - Е. I. Davidovskaya; A. S. Dubrovski; О. В. Zelmanski (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The necessity of early diagnosis of respiratory diseases, especially in the context of the COVID-19 pandemic, by means of pulse oximetric screening and monitoring has been substantiated. The expediency of using portable pulse oximeters by therapists and general practitioners has been shown. The main respiratory diseases accompanied by respiratory failure, which can be detected in time by pulse oximetry, are the chronic obstructive pulmonary disease and the obstructive sleep apnea-hypopnea syndrome. Early detection of these diseases is an important task because of the mild symptoms of these diseases in the early stages, and as a result, the prevalence of late diagnosis. Special attention is given to the pulse oximetry for COVID-19 detection, as this infection is also accompanied by respiratory failure. The use of oxygen concentrators and auto CPAP devices for the treatment of respiratory failure as well as rehabilitation has been argued. The effectiveness of the appointment of long-term oxygen therapy using oxygen concentrators for patients with chronic obstructive pulmonary disease, CPAP therapy using automatic CPAP devices for patients with obstructive sleep apnea-hypopnea syndrome with mandatory pulse oximetry monitoring has been confirmed. The analysis of 120 cases of treatment of moderate and severe COVID-19 cases complicated by the pneumonia has been carried out. The efficiency of the use of oxygen concentrators for supplying oxygen to patients at a flow rate not more than 5 l/min has been proven. It has been found that no more than 10 % of patients needed an oxygen flow rate more than 5 l/min. At the same time, the possibility of using CPAP devices for non-invasive ventilation of lungs using full-face masks has been shown. The expediency of using oxygen concentrators and CPAP devices for the rehabilitation of patients after COVID-19 has been noted.